Selección de los aspirantes a docentes en el cantón Latacunga - Aimara Pullupaxi, Luis Rosendo (2017)
This research is directly related to education quality, which is intended to develop in our country through a description process of candidates’ selection to teachers in Latacunga through a data collection; it has been achieved in some way to contribute with relevant information to the research of Basic Education career at Technical University of Cotopaxi. This research was developed to the socio-educational form, qualitative-quantitative, explanatory, bibliographic and documentary approach; by applying inductive, deductive, scientific, analytical and dialectical methods, which helped us to strengthen and apply in this research. For that reason, after the implementation of the surveys to directors, teachers and students, the research results showed that candidates´ selection to teachers in Latacunga is not done properly. The data obtained allowed to demonstrate that the selection process to the teachers is not adequate....